Preparation of Papers for the Study of Tobacco Advertising towards Malaysia Football Development - Rahiza, Ahmad Amirul Firdaus Ahmad; Rani, Mohd Khairul Azahari Abdul (International Journal of Engineering and Technology, 2018)
Advertising become one of the reasons that Malaysia football during the golden era age is famous and supporters get hype during every game. According to [13] During the peak of the football game in Malaysia, Dunhill is the brand that has the biggest scale in Advertising in 1980 â€“ 1990 before the tobacco banning in 2005. The studies also want to identify what approach Dunhill use before, during and after the tobacco banning to advertise their products. The research scope is also about how and why tobacco industries use football to spread brand awareness in Malaysia and how that lead to the Malaysia football quality. The objective of the research is to find out about the relationship between tobacco advertising and Malaysia football. In this case, the Dunhill product is chosen as a case study of tobacco brand because the company has contributed a lot of amount for sponsorship during the peak. Sports and sponsors especially football is a must, they need sponsors for the aid to support the event so the program can run smoothly and success [17]. Method of this research will be held in interview method which will be considered to interview former coach, sports analysis, and a player that is still available who played in the national team. Â This research can help us identify the contribution of tobacco advertising that gives the most impact in national football during the golden era. We can also find out about other brands that are also involved in contributing to making the football quality in Malaysia improves.